2016
DOI: 10.1177/2158244016631021
|View full text |Cite
|
Sign up to set email alerts
|

Making and Changing Wills

Abstract: Wills are important social, economic, and legal documents. Yet little is known about current will making practices and intentions. A comprehensive national database on the prevalence of will making in Australia was developed to identify who is or is not most likely to draw up a will and triggers for making and changing wills. A national survey of 2,405 adults aged above 18 years was administered by telephone in August and September 2012. Fifty-nine percent of the Australian adult population has a valid will, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…With regards to item C5, people may make provisions for their families or manage their assets and end of life care, without the presence of suicidal ideation. A study (Tilse et al, 2016 ) found that 59% of the general adult population had made wills. In a Malaysian population with its many cultural differences (Siau et al, 2017 ), certain cultural norms encourage bequeathing or the division of assets (Salisu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to item C5, people may make provisions for their families or manage their assets and end of life care, without the presence of suicidal ideation. A study (Tilse et al, 2016 ) found that 59% of the general adult population had made wills. In a Malaysian population with its many cultural differences (Siau et al, 2017 ), certain cultural norms encourage bequeathing or the division of assets (Salisu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Roles of peer educators and racial/ethnic community organizations might be important pathways to better access estate planning information and execution. Peer educators might be especially important when language barriers exist (Brooker, 2007;Tilse et al, 2016).…”
Section: Implications For Policies and Practicesmentioning
confidence: 99%
“…This study investigates racial and ethnic differences in estate planning and whether race/ethnicity moderates the associations of bequest expectations to leave an inheritance and charitable giving with the presence of a valid will among older adults living in the United States using a nationally representative dataset. The relationship with a valid will was chosen because it is one component of estate planning that is an important social, economic, and legal document (Tilse et al, 2016).…”
Section: Introductionmentioning
confidence: 99%